MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA PELAJARAN MATEMATIKA SDN 11 MERAPI BARAT - Jessy Ria Samfitri; Siti Dewi Maharani; Indra Gandi (Jurnal Inovasi Sekolah Dasar, 2021)
Abstract: This type of research is Classroom Action Research (CAR) which consists of planning, implementation, observation and reflection stages. This research was conducted at SDN 11 West Merapi, which is located at Tanjung Baru village, West Merapi district, Lahat district. The location of this school is Jln. Cross Sumatra Km. 16 SDN 11 West Merapi is a school managed by the government and led by the Principal named Edi Tomson, S. Pd. This research was conducted in the even semester of the 2020/2021 academic year. The research subjects were fourth grade students who found 16 students with 8 male students and 8 female students. Based on Classroom Action Research (CAR) it can be concluded that through problem-based learning models can improve student learning outcomes in mathematics subjects in fourth grade students of SDN 11 West Merapi. This is proven by student learning outcomes in each cycle carried out by researchers by determining the minimum completeness criteria  60, Cycle I completeness with a total of 6 out of 16 students and the current result is 37.5%, Cycle II completeness with 11 students from 16 students and the result of the presentation is 68.75% and in Cycle III the completeness of 13 students out of 16 students and the presentation result is 81.25% of the student's mastery learning results have reached the minimum completeness criteria.Keywords: Problem Based Learning, Learning Outcomes, MathematicsAbstrak: Jenis penelitian yang ini adalah Penelitian Tindakan Kelas (PTK) yang terdiri dari tahapperencanaan, pelaksanaan, pengamatan dan refleksi. Penelitian ini dilakukan di SDN 11 Merapi Barat yang beralamatkan di desa Tanjung Baru, Kecamatan Merapi Barat, Kabupaten Lahat Letak sekolah  ini Jln. Lintas Sumatera Km. 16 SDN 11 Merapi Barat merupakan sekolah yang dikelola oleh pemerintah dan dipimpin oleh Kepala Sekolah bernama Edi Tomson, S. Pd. Penelitian ini dilaksanakan pada semester genap tahun ajaran 2020/2021. Subjek penelitian yaitu siswa kelas IV yang berjumlah 16 orang siswa dengan 8 siswa laki-laki dan 8 siswa perempuan. Berdasarkan Penelitian Tindakan Kelas (PTK) dapat ditarik kesimpulan bahwa melalui model problem based learning dapat meningkatkan hasil belajar siswa pada mata pelajaran matematika pada siswa kelas IV SDN 11 Merapi Barat. Hal tersebut dibuktikan dengan meningkatnya hasil belajar siswa pada setiap siklus yang dilakukan peneliti dengan menentukan ketuntasan dari kriteria ketuntasan minimum 60, Siklus I ketuntasan dengan jumlah 6 siswa dari 16 siswa dan hasil presentase adalah 37,5%, Siklus II ketuntasan dengan jumlah  11 siswa dari 16 siswa dan hasil presentasinya adalah 68,75% dan pada Siklus III ketuntasan dengan jumlah 13 siswa dari 16 siswa dan hasil presentasinya adalah 81,25% dari hasil ketuntasan belajar siswa telah mencapai kriteria ketuntasan minimum.Kata Kunci : Problem Based Learning, Hasil Belajar, Matematika